Achieving Lethal Effects by Small Unmanned Aerial Vehicles: Opportunities and Limitations. Issue 1 (2nd January 2019) - Watling, Jack; Waters, Nicholas
Abstract : The military application of armed small unmanned aerial vehicles (SUAVs) has been discussed for over a decade. Many of their imagined uses however overlook crucial limitations on their employment relating to power, processing, payload, cost, and control systems. Over the last three years armed SUAVs have been extensively employed on the battlefield, providing a rich set of case studies. Jack Watling and Nicholas Waters explore how armed SUAVs can be effectively integrated into the British Army.